2016
DOI: 10.1002/bjs.10205
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for requiring cholecystectomy for gallstone disease in a prospective population-based cohort study

Abstract: BackgroundThe relationship between different lifestyle factors and the risk of needing cholecystectomy for gallstone disease is not clear. This study aimed to assess the association between anthropometric, lifestyle and sociodemographic risk factors and the subsequent risk of requiring cholecystectomy for gallstone disease during long‐term follow‐up in a defined population cohort.MethodsData from a large population‐based cohort study performed from 1995 to 1997 were used (the second Norwegian Nord‐Trøndelag he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…9 Similar findings were seen in the studies by Talseth, in Sweden, in 2016 and Stender in 2013 in which a causal association between elevated BMI and increased risk of symptomatic gallstone disease was seen. 14,15 But a study by Hui Sun et al in 2009 (China) stated that the causal association is gender specific and obese women are more significantly associated with gallstone disease compared to obese men. 13 In the present study, 56.52% patients had mixed diet as compared to 43.48% patients with vegetarian diet but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…9 Similar findings were seen in the studies by Talseth, in Sweden, in 2016 and Stender in 2013 in which a causal association between elevated BMI and increased risk of symptomatic gallstone disease was seen. 14,15 But a study by Hui Sun et al in 2009 (China) stated that the causal association is gender specific and obese women are more significantly associated with gallstone disease compared to obese men. 13 In the present study, 56.52% patients had mixed diet as compared to 43.48% patients with vegetarian diet but this association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Vigorous aerobic exercise (measured by history of running distance) and cardiorespiratory fitness (an independent predictor of liver fat 141 ) are both inversely related to gallstone disease risk. 144 Also in women, vigorous exercise is associated with a decreased rate of cholecystectomy, 145 an additional potential risk factor for NAFLD. 143 Recreational physical activity is inversely related to risk of asymptomatic gallstones in adult women.…”
Section: Physical Activity and Gallbladder Diseasementioning
confidence: 99%
“…143 Recreational physical activity is inversely related to risk of asymptomatic gallstones in adult women. 144 Also in women, vigorous exercise is associated with a decreased rate of cholecystectomy, 145 an additional potential risk factor for NAFLD. 146 Of note, an increment of cardiorespiratory fitness by one MET reduces the odds of suffering from gallstone disease by 8% in men and 13% in women.…”
Section: Physical Activity and Gallbladder Diseasementioning
confidence: 99%
“…In the paediatric population this increase has been attributed to increases in BMI 3 . Population based studies have also identified an increased BMI as a risk factor for subsequent cholecystectomy 4 . As a result the number of procedures for gallstone disease has risen with cholecystectomy becoming the most common elective surgical procedure in the United States 1 .…”
Section: Introductionmentioning
confidence: 99%